Structure and expression of the guinea pig preproenkephalin gene: site-specific cleavage in the 3' untranslated region yields truncated mRNA transcripts in specific brain regions. - LaForge, K S (1995)
We isolated the guinea pig preproenkephalin gene from a genomic library by hybridization to a rat cDNA probe. The entire nucleotide sequence of the gene was determined. Genomic Southern blot hybridization demonstrated that the gene exists in a single copy within the genome. On the basis of RNase protection transcript mapping and homology comparisons with known preproenkephalin sequences from other species and assuming a poly(A) tail length of 100 residues, we predicted an mRNA transcript of approximately 1,400 nucleotides encoded by three exons. Northern (RNA) blot analysis of total RNA from several brain regions showed high levels of preproenkephalin mRNA in the caudate putamen, nucleus accumbens, and hypothalamus, with detectable levels in the amygdala, ventral tegmental area, and central gray and also in the pituitary. Unexpectedly, in several brain regions, the mRNA appeared not only in the 1,400-nucleotide length but also in a shorter length of approximately 1,130 bases. Significant amounts of the shorter mRNA were found in the caudate putamen, nucleus accumbens, and amygdala. The longer, but not the shorter, transcripts from the caudate putamen were found to be polyadenylated, but the difference in size was not due solely to the presence of poly(A) tails. Northern gel analysis of total RNA from the caudate putamen with probes from each exon, together with RNase protection mapping of the 3' end of the mRNA demonstrated that the 1,400-base preproenkephalin mRNA transcripts are cleaved in a site-specific manner in some brain regions, yielding a 1,130-base transcript and a 165-base polyadenylated fragment derived from the terminal end of the 3' untranslated region of the mRNA. This cleavage may serve as a preliminary step in RNA degradation and provide a mechanism for control of preproenkephalin mRNA abundance through selective degradation.